Electrical conductivity mapping in relation to clay of a Ferralsol under no tillage system - Machado, Pedro Luiz Oliveira de Almeida; Bernardi, Alberto Carlos de Campos; Valencia, Luís Ivan Ortiz; Molin, José Paulo; Gimenez, Leandro Maria; Silva, Carlos Alberto; Andrade, Aluísio Granato de; Madari, Beáta Emoke; Meirelles, Margareth Simões Penello (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to map and evaluate the spatial variability of the soil electrical conductivity (EC), measured with a contact sensor in a Rhodic Ferralsol under no till grain crops. The values of soil EC were related to soil clay content, measured by the densimetric method in georreferenced samples collected at 0–5 and 5–10 cm, in a 13 ha field. Soil samples were collected using a 40x40 m grid and densed grids of 20, 10 and 5 m spacing. Spatial continuity of EC and of clay content was modeled using semivariograms. Soil EC ranged from 1.9 to 13.7 mS m-1 with an average of 5.2 mS m-1 and coefficient of variation of 48%. The kriged map of soil EC pointed out a tendency of increase where clay levels were higher. Determination coefficients between soil EC and clay content were 0.78 and 0.77, respectively for 0–5 and 5–10 cm depth. The EC map adequatly reflects the spatial variation in soil texture for establishing the limits of management zones.